14-3-3ζ: A numbers game in adipocyte function?. (2nd April 2016) - Lim, Gareth E.; Johnson, James D.
ABSTRACT: Molecular scaffolds are often viewed as passive signaling molecules that facilitate protein-protein interactions. However, new evidence gained from the use of loss-of-function or gain-of-function models is dispelling this notion. Our own recent discovery of 14-3-3ζ as an essential regulator of adipogenesis highlights the complex roles of this member of the 14-3-3 protein family. Depletion of the 14-3-3ζ isoform affected parallel pathways that drive adipocyte development, including pathways controlling the stability of key adipogenic transcription factors and cell cycle progression. Going beyond adipocyte differentiation, this study opens new avenues of research in the context of metabolism, as 14-3-3ζ binds to a variety of well-established metabolic proteins that harbor its canonical phosphorylation binding motifs. This suggests that 14-3-3ζ may contribute to key metabolic signaling pathways, such as those that facilitate glucose uptake and fatty acid metabolism. Herein, we discuss these novel areas of research, which will undoubtedly shed light onto novel roles of 14-3-3ζ, and perhaps its related family members, on glucose homeostasis.